DEVELOPING SEESAW AS MEDIA BASED ON SCIENTIFIC APPROACH FOR TEACHING SPEAKING OF RECOUNT TEXT FOR GRADE TEN STUDENTS AT SMA SWASTA TRITUNGGAL TANJUNGBALAI - Debora Friskila Sinaga; Rahmad Husein (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2021)
This study was aimed to develop Seesaw as media based on Scientific Approach for teaching speaking of recount text for grade ten at SMA Swasta Tritunggal Tanjungbalai. This study was conducted by Research and Development (R&D) design through six stages; gathering data and information, conducting needs analysis, designing Seesaw as media based on Scientific Approach, validating the product to the experts, revising the product, and releasing Seesaw as media as the final product. The subjects of the study were the English teacher and grade ten students of SMA Swasta Tritunggal Tanjungbalai. The data were gathered by document study, interviewing the English teacher, and distributing questionnaires to grade ten students of science class that consisted of 26 students to get the students’ needs. The product (Seesaw) had validated by two experts, namely; an English lecturer and an English teacher. The overall assessment showed that the developed Seesaw was valid to be used for teaching spoken recount text by obtaining an average score of 4.46 or 89.2% and it was categorized as “very good”.